2018
DOI: 10.3390/w10091233
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Analysis Reveals the Importance of Riparian Resources as Carbon Subsidies for Fish Species in the Daning River, a Tributary of the Three Gorges Reservoir, China

Abstract: The patterns of carbon flow in large rivers influenced by dams are still not well known. We hypothesized that spatial variation in fish assimilation of basal production sources would be affected by heterogeneity of landscape-scale hydrology within a watershed due to the impoundment. We used stable isotope analysis and Bayesian mixing models to estimate relative contributions of basal production sources to fish consumers in a tributary of the Three Gorges Reservoir (TGR) with remarkably heterogeneous habitats b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…These fish species could integrate the food carbon source from the mainstream. On the other hand, although the former study has verified that riparian C3 plants are the main basal food source irrespective of reaches or feeding groups (Deng et al, 2018), the CRs, which are indicative of food source diversity in the backwater area are significantly larger than those in the upper lotic reaches (Fig. 4).…”
Section: Longitudinal Patterns Of Trophic Diversity In Fish Assemblagesmentioning
confidence: 80%
See 3 more Smart Citations
“…These fish species could integrate the food carbon source from the mainstream. On the other hand, although the former study has verified that riparian C3 plants are the main basal food source irrespective of reaches or feeding groups (Deng et al, 2018), the CRs, which are indicative of food source diversity in the backwater area are significantly larger than those in the upper lotic reaches (Fig. 4).…”
Section: Longitudinal Patterns Of Trophic Diversity In Fish Assemblagesmentioning
confidence: 80%
“…Smaller NND and SDNND indicate greater trophic redundancy, which means, groups have more similar trophic niches (Abrantes et al, 2014; Masese et al, 2018). Because riparian plants are the major carbon source to fishes and widespread along the river channel (Deng et al, 2018), the range in potential source δ 13 C was similar for all sites, meaning that the community-wide metrics are comparable among sites and periods (Layman et al, 2007a). In order to provide more robust metrics that are unbiased with respect to variations in the number of groups and allow for statistical comparisons among sites and periods, Bayesian methodology was implemented to generate a posterior distribution of estimates of these metrics, thus providing a measure of uncertainty of these metrics for the fish communities at each site and period (Jackson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the where the geological location, geometry, hydrological pattern, system productivity, floodplain size and land use characteristics differ greatly (Wang et al, 2014). These conditions may explain the contrasting findings in the literature (Clapcott, 2003;Deng et al, 2018;Doi, 2009) and could also explain why these results differ from those found in other relatively close reservoirs within the La Plata Basin (Hoeinghaus et al, 2007). Moreover, the age of the impoundment may also play a role determining a higher allochthonous subsidy in the first years of creation (situation of our studied system) than in older impoundments.…”
Section: Discussionmentioning
confidence: 99%